Letter to City Council from City Manager Edmund F. Sotelo - Edmund F. Sotelo:::::: (2001)
A letter sent to the Oxnard city council from city manager Edmund F. Sotelo discussing the impacts of a casino in Oxnard, California. Includes a letter sent by the Greenville Rancheria of Maidu Indians.